PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP EARNING PER SHARE PADA PERUSAHAAN LQ45 YANG TERDAFTAR DI BEI TAHUN 2017-2019 - Landy, Edy; Muliana, Sitti (Patria Artha Journal of Accounting dan Financial Reporting, 2022)
The purpose of this research is to determine the effect of Corporate Social Responsibility Disclosure on Earning Per Share of LQ45 Companies Listed on the IDX in 2017-2019. The type of data used in this study is quantitative data. The source of data used in this research is secondary data. The method of analysis used is descriptive data, classical assumptions and t test. The results of this study indicate that Corporate Social Responsibility has a significant effect on Earning Per Share of LQ45 Companies listed on the IDX in 2017-2019.